Creep characteristics of sandstone during freezing/thawing process - Yongjun SONG; Jinghui CAO; Keyan CHENG; Huimin YANG; Ran BI; Kun ZHANG (Shuiwen dizhi gongcheng dizhi)
The rock mass in cold regions is always subjected to the load and freeze-thaw. If the impact of long-term freeze-thaw mechanical behavior on sandstone mass is neglected, it would lead to significant hazards to the construction and safe operation of engineering in cold regions. This study focused on the sandstone from a slope engineering in the cold region. The realistic long-term mechanical response characteristics of engineering rocks in cold regions was presented by uniaxial graded loading creep tests for the freezing/thawing process at different freezing temperatures and the same stress state. Then the effect of the freezing/thawing process on the long-term mechanical properties of the rock mass was investigated, and the macroscopic mechanical indexes, such as creep strain, steady-state creep rate, and long-term strength, were analyzed quantitatively. The results indicate that sandstone undergoes the stages of cold shrinkage, frost heave, and steady-state creep during the freezing process, and the stages of thaw consolidation and steady-state creep during the thawing process. Sandstone shrinkage deformation occurs during the cold shrinkage and thawing stages, while expansion deformation occurs during the frost heave stage. At freezing/thawing temperatures of −5 °C/25 °C, −10 °C/25 °C, and −15 °C/25 °C, compared to the creep strains at room temperature, the creep strains of the sandstone are amplified by 102%−193%, 81%−126%, and 105%−194%, respectively. The steady-state creep rate after thawing increases by 3.65, 4.31, and 5.56 times compared to the steady-state creep rate at room temperature. The long-term strength of the sandstones in the frozen/thawed state are 96.33%, 88.52%, and 75.44% of the long-term strength at room temperature, respectively. Stress inhibits the generation of cold shrinkage and freezing deformations and promotes the generation of thawing deformations. The freezing temperature affects frost heave deformation and thaw shrinkage deformation after thawing. As the freezing temperature decreases, the deformation increases. A test method combining creep with freeze-thaw processes has been proposed in the study, which can characterize the real engineering condition. This study provides a new method to evaluate the long-term stability of rock mass engineering in cold regions.